Sierra Leone : Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents the status report on preparatory activities for the full Poverty Reduction Strategy Paper (PRSP) for Sierra Leone. The governance and institutional arrangements proposed in the interim PRSP (I-PRSP) for the preparation of the full PRSP have all been set up and are currently functioning. The I-PRSP focused on a small number of realistic and meaningful indicators and targets. However, these monitoring indicators will be expanded during the preparation of the full PRSP to include qualitative indicators, which will be identified during the Focus Group Discussions and Participatory Poverty Assessments Consultations.